Biasing Buckling Direction in Shape‐Programmable Hydrogel Sheets with Through‐Thickness Gradients. (26th September 2019) - Zhou, Ying; Duque, Carlos M.; Santangelo, Christian D.; Hayward, Ryan C.
Abstract: A photocrosslinkable poly( N, N ′‐diethylacrylamide) copolymer allows for the photolithographic fabrication of hydrogel sheets with nonuniform crosslinking density and swelling ratio. Using this material system, different 3D shapes with nonzero Gaussian curvature K are successfully programmed by prescribing a "metric" defined by in‐plane variations in swelling. However, this methodology does not control the direction of buckling adopted by each positive K feature, and therefore cannot controllably select between different isometric shapes defined by a single metric. Here, by introducing gradients in swelling through the thickness of the gel sheet by tuning the absorption of the UV‐light used for crosslinking, a preferential buckling direction is locally specified for each feature by the direction of UV exposure. By also controlling the strength of coupling between neighboring features, this is shown to be an effective method to program buckling direction of each unit within a canonical corrugated surface shape. Abstract : Photocrosslinkable copolymers allow for the photolithographic fabrication of hydrogels with nonuniform swelling ratio, which results in 2D to 3D shape morphing. Here, not only in‐plane variations in swelling but also gradients through the gel sheet thickness are introduced to pattern a canonical corrugated surface shape with controllable buckling direction of each unit.